Benefits of team participative decision making and its potential to affect individual creativity. Issue 7 (8th May 2018) - Wong, Yin Yee; Chow, Irene Hau‐Siu; Lau, Victor P.; Gong, Yuanyuan
Abstract: How does team participative decision‐making affect individual creative performance? Building on team climate theory (Anderson & West, 1998; West 1990, 2002; West & Sacramento, 2012), this study investigates the indirect effect of team participative decision making on employee creativity through individual perception of cognition team diversity and psychological safety. Results from 256 supervisor–subordinate dyads in 45 teams show that team participative decision making is positively associated with cognitive team diversity and psychological safety. For the mediating effects, team participative decision‐making climate is positively indirectly related to creative performance via psychological safety but not via cognitive team diversity. Theoretical and practical implications are discussed.